Characteristics, Antihyperglycemics Utilization, and Quality of Life in Patients with Type 2 Diabetes Mellitus Admitted to a Primary Health Center - Nasution, Azizah; Simbolon, Rany; Tanjung, Hari Ronaldo (Indonesian Journal of Pharmaceutical and Clinical Research, 2018)
Abstract. This study aimed to assess the characteristics, utilization of antihyperglycemic drugs, and to analyze the quality of life (QOL) in type 2 diabetes mellitus (T2DM) patients. This two-month prospective descriptive cross-sectional study was undertaken by distributing the European Quality of Life - 5 Dimensions 3 Level (EQ-5D-3L) questionnaire to the patients with T2DM (n=50) admitted to Helvetia primary health center Medan to assessed their QOL. The patients’ characteristics and the utilization of antihyperglycemic drugs were assessed from the patients’ medical records using a self-designed questionnaire. The inclusion criteria were T2DM patients with age of 18 years or older, had no mental disorders, and agreed to sign the informed consent. The patients’ characteristics, their QOL, utilization of antihyperglycemic drugs, and association among their characteristics and QOL were analyzed using descriptive and Chi-Square tests. All analyses were performed using the Statistical Package for the Social Sciences (SPSS, version 19, Chicago, IL, USA) (p value <0.05 was considered significant). It was found that the mean age of the T2DM patients was 59.70 ± 10.44 (years). Most (66%) of them were females. Majority (80%) of the patients graduated from primary to senior high schools. Nearly half (44%) of the patients was provided glibenclamide. The mean QOL of the patients was 0.79 ± 0.14. There was no significant association between the patients’ QOL and their characteristics (p values >0.05). This study proved that most of the T2DM patients were females. Glibenclamide was the most frequently prescribed drug for the patients. The QOL of the patients was 79% of full health. Keyword: Antihyperglycemic Drugs , EQ-5D, QOL, T2DM